Identification of LncRNA Prognostic Signature Associated With Genomic Instability in Pancreatic Adenocarcinoma - Zhu, Jinfeng; Huang, Qian; Peng, Xingyu; Luo, Chen; Liu, Sicheng; Liu, Zitao; Wu, Xun; Luo, Hongliang (Frontiers in Oncology, 2022)
Background: Genomic instability (GI) is an important feature of cancer, and plays a key role in the occurrence and development of Pancreatic adenocarcinoma (PAAD). Long non-coding RNA (LncRNA) is involved in regulating GI and is an emerging prognostic biomarker. Recently, researchers used such GI-related LncRNAs (GILncRNAs) to establish a prognostic signature for some cancer patients, which helps predict their overall prognosis. However, patients with PAAD lack this prognostic signature constructed with GILncRNA. Methods: We screened GILncRNAs from 182 patients with PAAD and established a co-expression network. Then, we used GILncRNAs with survival information to construct a prognostic signature by multivariate Cox regression analysis. Next, we assessed our signature through survival analysis, mutation correlation analysis, independent prognostic analysis, and clinical stratification analysis in the training set, and validated them in the testing set and all TCGA set. We performed external clinical relevance validation of the signature and validated the effect of AC108134.2 in GILncSig on PAAD by in vitro experiments. Finally, we explored the function of GILncRNA signature (GILncSig) dependent on Gene Ontology enrichment analysis and performed chemotherapeutic drug sensitivity analysis. Results: We identified 409 GILncRNAs, 5 of which constituted our prognostic risk signature. They were AC095057.3, AC108134.2, AC124798.1, AL606834.1 and AC104695.4, respectively. Our signature was better than others in predicting overall survival and applied to patients with PAAD of all ages, genders, and tumor grades. In the GSE102238, our signature was correlated with tumor length, and tumor stage of patients with PAAD. In vitro, functional experiments were used to validate that AC108134.2 is associated with PAAD genomic instability and progression. Interestingly, pRRophetic analysis demonstrated that the high-risk group possessed reverse characteristics was sensitive to chemotherapy. Conclusions: This risk signature has good prognostic performance and may become a potential sensitive biological indicator of PAAD chemotherapy, which will help clinical decision-making and management.